Characterization of the rhp7(+) and rhp16(+) genes in Schizosaccharomyces pombe. - Lombaerts, M (1999)
The global genome repair (GGR) subpathway of nucleotide excision repair (NER) is capable of removing lesions throughout the genome. In Saccharomyces cerevisiae the RAD7 and RAD16 genes are essential for GGR. Here we identify rhp7 (+), the RAD7 homolog in Schizosaccharomyces pombe. Surprisingly, rhp7 (+)and the previously cloned rhp16 (+)are located very close together and are transcribed in opposite directions. Upon UV irradiation both genes are induced, reaching a maximum level after 45-60 min. These observations suggest that the genes are co-regulated. Schizo-saccharomyces pombe rhp7 or rhp16 deficient cells are, in contrast to S.cerevisiae rad7 and rad16 mutants, not sensitive to UV irradiation. In S.pombe an alternative repair mechanism, UV damage repair (UVDR), is capable of efficiently removing photolesions from DNA. In the absence of this UVDR pathway both rhp7 and rhp16 deficient cells display an enhanced UV sensitivity. Epistatic analyses show that rhp7 (+)and rhp16 (+)are only involved in NER. Repair analyses at nucleotide resolution demonstrate that both Rhp7 and Rhp16, probably acting in a complex, are essential for GGR in S.pombe.